Protective effect of bromelain on corrosive burn in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ (ELSEVIER SCI LTD, 2021)
Introduction: In some cases, the tongue and oesophagus tissues are damaged by the corrosive burn. Surgical interventions may cause scar formation, and severe burns treatment methods are limited. This study aims to investigate bromelain, a phytotherapeutic product, on the corrosive burn as a non-surgical option and as an adjunctive therapy, insofar as the treatment of corrosive wounds is not limited only to the treatment of oxidative stress and inflammatory reactions. Methods: On the tongues of Wistar albino rats, chemically produced oral ulcers were created by topical application of NaOH (40%) solution, and in the distal oesophagus same mixture was applied to produce a corrosive oesophageal burn. For a week, they were treated orally by bromelain (100 mg/kg/day) or saline solution. At the end of seven days, animals were decapitated to remove the tongue and oesophagus, and blood samples were collected to obtain serum. Myeloperoxidase (MPO) activity, malondialdehyde (MDA), glutathione (GSH), interleukin-1 beta (IL-1 beta) and tumour necrosis factor-alpha (TNF-alpha) concentrations were measured in serum, and luminol and lucigenin chemiluminescence (CL) were measured in tissue samples. Results: MDA and CL values were significantly increased, and GSH levels in tissue significantly decreased due to the corrosive burns. Saline treated corrosive burn group measured higher in the serum cytokines in according to the control group. Conclusions: Bromelain administration decreased oxidant and inflammatory parameters and increased antioxidant levels in NaOH-induced corrosive burns. Thus, we concluded that bromelain may protect the tongue and oesophagus tissues with its anti-inflammatory and antioxidant effects. (C) 2020 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Bromelain; Corrosive burn; Oesophagus; Inflammation; Tongue; STRICTURE FORMATION; OXIDATIVE STRESS; INJURY